Accuracy and Reproducibility of Myocardial Blood Flow Quantification by Single Photon Emission Computed Tomography Imaging in Patients With Known or Suspected Coronary Artery Disease. (8th June 2022) - de Souza, Ana Carolina do A.H.; Harms, Hendrik J.; Martell, Laurel; Bibbo, Courtney; Harrington, Meagan; Sullivan, Kyle; Hainer, Jon; Dorbala, Sharmila; Blankstein, Ron; Taqueti, Viviany R.; Foley Kijewski, Marie; Park, Mi-Ae; et al.
Abstract : Background: Single photon emission computed tomography (SPECT) has limited ability to identify multivessel and microvascular coronary artery disease. Gamma cameras with cadmium zinc telluride detectors allow the quantification of absolute myocardial blood flow (MBF) and myocardial flow reserve (MFR). However, evidence of its accuracy is limited, and of its reproducibility is lacking. We aimed to validate 99m Tc-sestamibi SPECT MBF and MFR using standard and spline-fitted reconstruction algorithms compared with 13 N-ammonia positron emission tomography in a cohort of patients with known or suspected coronary artery disease and to evaluate the reproducibility of this technique. Methods: Accuracy was assessed in 34 participants who underwent dynamic 99m Tc-sestamibi SPECT and 13 N-ammonia positron emission tomography and reproducibility in 14 participants who underwent 2 99m Tc-sestamibi SPECT studies, all within 2 weeks. A rest/pharmacological stress single-day SPECT protocol was performed. SPECT images were reconstructed using a standard ordered subset expectation maximization (OSEM) algorithm with (N=21) and without (N=30) application of spline fitting. SPECT MBF was quantified using a net retention kinetic model‚ and MFR was derived as the stress/rest MBF ratio. Results: SPECT global MBF with splines showed good correlation with 13 N-ammonia positron emission tomography (r=0.81, P <0.001) and MFR estimates (r=0.74, P <0.001). Correlations were substantially weaker for standard reconstruction without splines (r=0.61, P <0.001 and r=0.34, P =0.07, for MBF and MFR, respectively). Reproducibility of global MBF estimates with splines in paired SPECT scans was good (r=0.77, P <0.001), while ordered subset expectation maximization without splines led to decreased MBF (r=0.68, P <0.001) and MFR correlations (r=0.33, P =0.3). There were no significant differences in MBF or MFR between the 2 reproducibility scans independently of the reconstruction algorithm ( P >0.05 for all). Conclusions: MBF and MFR quantification using 99m Tc-sestamibi cadmium zinc telluride SPECT with spatiotemporal spline fitting improved the correlation with 13 N-ammonia positron emission tomography flow estimates and test/retest reproducibility. The use of splines may represent an important step toward the standardization of SPECT flow estimation.